2015
DOI: 10.1097/ipc.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, Hospital Costs, Payments, and Readmissions Associated With Clostridium difficile Infection Among Medicare Beneficiaries

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
(14 reference statements)
0
23
0
1
Order By: Relevance
“…Un hallazgo interesante en nuestro estudio fue la no asociación con mayor mortalidad, estancia hospitalaria ni estancia en la UCI entre casos y controles, a diferencia de lo reportado en otras series, donde la infección por C. difficile también se ha asociado a rehospitalizaciones 16 . Sin embargo, esta diferencia pudiera estribar en el número de los casos de esta serie, el uso de antibióticos activos contra C. difficile en forma temprana y el egreso de los pacientes en forma precoz para continuar manejo en casa.…”
Section: Discussionunclassified
“…Un hallazgo interesante en nuestro estudio fue la no asociación con mayor mortalidad, estancia hospitalaria ni estancia en la UCI entre casos y controles, a diferencia de lo reportado en otras series, donde la infección por C. difficile también se ha asociado a rehospitalizaciones 16 . Sin embargo, esta diferencia pudiera estribar en el número de los casos de esta serie, el uso de antibióticos activos contra C. difficile en forma temprana y el egreso de los pacientes en forma precoz para continuar manejo en casa.…”
Section: Discussionunclassified
“…Drozd found 1.9% 30-day attributable mortality after hospital-onset CDI, although their analysis included younger beneficiaries (i.e., end-stage renal disease, disabled). 8 Shorr reported attributable CDI mortality of 14.9% at 60 days and 19.2% at one year in the elderly. 9 Prior studies estimating the risk of mortality due to CDI have not considered the possibility of effect modification, in which the risk is not uniform but varies depending on other factors.…”
mentioning
confidence: 99%
“…Symptomatic first recurrence after resolution of the primary CDI episode occurs in 20%–30% of patients, usually within 30 days after treatment cessation [3–5]. Clostridium difficile infection mortality estimates vary widely in the literature, with rates ranging from less than 5% to more than 20% in severe cases [6, 7]. A review of 27 studies found that the CDI-associated mortality rate was 6% within 3 months of diagnosis [8].…”
mentioning
confidence: 99%